Lithium carbon dioxide battery with homogeneous and heterogeneous synergetic catalysis

Through the coordinated catalysis of bismuth-oxyhalogenic photoelectric positive electrode and halogen lithium salt in lithium carbon dioxide batteries, the problem of difficulty in formation and decomposition of Li2CO3 and instability of photoelectric positive electrode in lithium carbon dioxide batteries is solved, and the cycle stability and electrochemistry of the battery are improved performance.

CN119231036AActive Publication Date: 2024-12-31NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411457751.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-31
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

Li2CO3, the discharge product of lithium carbon dioxide batteries, is a wide band gap insulating material, which leads to slow kinetics of carbon dioxide reduction reaction and carbon dioxide precipitation reaction, and the photoelectric positive electrode is unstable during the cycle, with high overpotential and low cycle life.

Method used

Using homogeneous heterogeneous synergistic catalysts, including bismuth-oxyhalogen photoelectrode Bi5O7X/CP and organic ether electrolytes of halogen lithium salts, the photoelectricity is improved through the layered crystal structure of bismuth-oxyhalogen substances and the incorporation of halogen lithium salts. Stability and cycle life of the positive electrode.

Benefits of technology

It significantly reduces the difficulty of forming and decomposition of Li2CO3, improves the stability and life of the photoelectric positive electrode, reduces the overpotential, and enhances the electrochemical performance and cyclic stability of lithium carbon dioxide batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119231036A_ABST
    Figure CN119231036A_ABST
Patent Text Reader

Abstract

The invention discloses a homogeneous and heterogeneous synergetic catalysis lithium carbon dioxide battery. According to the invention, bismuth oxyhalide / carbon paper with a layered crystal structure is used as a photoelectric positive electrode, and an organic ether solvent added with halogen lithium salt is used as an electrolyte to enhance the photo-assisted lithium carbon dioxide battery. Bismuth oxyhalide substances generate rich electron hole pairs under the action of a light field, so that the forming and decomposing difficulty of Li2CO3 in the charging and discharging process is remarkably reduced. Due to the doping of the halogen lithium salt, the photoelectric positive electrode is easier to react on a solid-liquid interface, so that the photoelectric positive electrode can stably and continuously work. And the halogen lithium salt is also beneficial to carrier separation, so that the photo-assisted lithium carbon dioxide battery is ensured to keep a relatively low non-functional barrier in the whole cycle period. Through the synergistic effect of the positive electrode and the electrolyte, the service life of the photoelectric positive electrode is remarkably prolonged, the stability of the photoelectric positive electrode is remarkably improved, the forming / decomposing difficulty of a discharging product Li2CO3 in the discharging / charging process of the lithium-carbon dioxide battery is greatly reduced, the overpotential of the lithium-carbon dioxide battery is reduced, and the electrochemical performance and the cycling stability of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium carbon dioxide batteries, and in particular to a lithium carbon dioxide battery with homogeneous and heterogeneous synergistic catalysis. Background Art

[0002] As a unique energy storage device for carbon dioxide storage and conversion, lithium carbon dioxide batteries are expected to alleviate a series of environmental problems caused by the continuous burning of fossil fuels, such as the greenhouse effect. Generally, the theoretical energy density of lithium carbon dioxide batteries is as high as 1876Whkg -1 , which is considered to be one of the next generation of energy storage devices and has potential application prospects in many scenarios. However, the discharge product of lithium carbon dioxide batteries, Li2CO3, is a wide bandgap insulating material that is thermodynamically stable, resulting in slow kinetics of carbon dioxide reduction reaction (CO2RR) and carbon dioxide evolution reaction (CO2ER). Therefore, it is crucial to seek a new method to promote the formation and decomposition of Li2CO3 to achieve stable and durable lithium carbon dioxide batteries.

[0003] External solar-driven lithium-carbon dioxide batteries are a very promising and attractive strategy. Under illumination, the photocatalyst at the cathode effectively captures photons, at which time the active photoexcited electrons and holes act on the redox of CO2, respectively, thereby reducing the voltage hysteresis and improving the reversibility of the battery. However, as the cycle progresses, the photocathode becomes very unstable, especially in a continuous strong oxidizing environment brought about by photogenerated holes. The photon utilization rate decreases, and the photocathode gradually loses its original performance. Therefore, there is an urgent need to design a strategy to effectively extend the life of the photocathode. Summary of the invention

[0004] In order to solve the problems of the prior art, the purpose of the present application is to provide a homogeneous and heterogeneous synergistic catalyst for light-assisted lithium carbon dioxide batteries and its preparation method and application, so as to solve the problems of high overpotential and low cycle life of lithium carbon dioxide batteries in the prior art.

[0005] In order to solve the problems of the prior art, the technical solution adopted by the present invention is:

[0006] A lithium carbon dioxide battery with homogeneous and heterogeneous synergistic catalysis comprises a positive electrode, a separator, a negative electrode and an electrolyte, wherein the positive electrode is a bismuth oxyhalogen photoelectric positive electrode Bi5O7X / CP, the electrolyte is an organic ether electrolyte added with a lithium salt, and the negative electrode is a lithium foil, wherein the lithium salt comprises lithium bistrifluoromethanesulfonyl imide with a final concentration of 1 mol / L and LiX with a final concentration of 0.05 mol / L, and X is Cl, Br or I.

[0007] As an improvement, the diaphragm is a glass fiber diaphragm GF / D.

[0008] As an improvement, the organic ether electrolyte comprises a mixture of one or more of cyclopentane, diethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.

[0009] As an improvement, the bismuth oxyhalide photoelectric positive electrode Bi5O7X / CP is prepared by mixing the active material Bi5O7X, polyvinylidene fluoride binder PVDF and Ketjen Black in a mass ratio of 8:1:1 and adding them to n-methyl-2-pyrrolidone liquid to form a uniform slurry, which is then coated on a carbon paper disc and dried in a vacuum drying oven at 120°C for 12 hours.

[0010] A further improvement is that the preparation method of the Bi5O7X is: dissolving Bi(NO3)3·5H2O and NaOH in distilled water to form a white mixture; then adding KX solution to the white mixture, stirring for 30 minutes, heating at 180°C for 24 hours, cooling to room temperature, collecting the precipitate by centrifugation, washing it with deionized water and ethanol three times respectively, and drying it in a drying oven at 60°C.

[0011] As a further improvement, the final concentration of Bi(NO3)3 in the white mixture is 0.2 mol / L, the final concentration of NaOH is 0.6 mol / L, and the final concentration of KX is 0.08 mol / L.

[0012] As an improvement, the working environment of the homogeneous and heterogeneous synergistic catalytic lithium carbon dioxide battery is: the area of ​​the cut bismuth oxygen halogen photoelectric positive electrode Bi5O7X / CP is 1.13cm 2 , and the effective lighting area is 0.5cm 2 , the flow rate of CO2 is 0.05mL / min.

[0013] Beneficial effects:

[0014] Compared with the prior art, the present invention is a lithium carbon dioxide battery with homogeneous and heterogeneous synergistic catalysis, which uses bismuth oxyhalide / carbon paper with a layered crystal structure as a photoelectric cathode and an organic ether solvent with added halogen lithium salt as an electrolyte to enhance the light-assisted lithium carbon dioxide battery. As a p-type semiconductor, bismuth oxyhalide substances produce abundant electron-hole pairs under the action of the light field, which significantly reduces the formation and decomposition difficulty of Li2CO3 during the charge and discharge process. Due to the incorporation of halogen lithium salts in the electrolyte, the photoelectric cathode is more likely to react with holes at the solid-liquid interface. The more significant photocurrent response of the Bi5O7I photoelectric cathode and lithium iodide can be attributed to the more densely separated photocharges, indicating that the holes are more likely to react with I -The photocathode reacts instead of recombining with electrons, thus enabling the photocathode to work stably and continuously. In addition, the halogen lithium salt also helps to separate the charge carriers, so that the light-assisted lithium carbon dioxide battery maintains a low overpotential throughout the cycle. The lithium carbon dioxide battery using the Bi5O7I photocathode at a current density of 0.01 mA cm -2 Under the light condition, it shows an ultra-high discharge voltage platform of 3.05V, which exceeds the equilibrium potential of product formation (2.80Vvs. Li + / Li), indicating that light energy is continuously output in the form of electrical energy. Compared with batteries without lithium iodide, the solid-liquid synergistic light-assisted battery did not show a decrease in efficiency even after 20 cycles. This shows that the complementary advantages of the two catalysts can significantly improve the life and stability of the photoelectric positive electrode, reduce the overpotential of the lithium carbon dioxide battery, and improve the electrochemical performance and cycle stability of the battery, which has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Schematic diagram of the structure of Bi5O7I crystal;

[0016] Figure 2 This is a scanning electron microscope image of Bi5O7I;

[0017] Figure 3 is the X-ray diffraction pattern of Bi5O7I;

[0018] Figure 4 Schematic diagrams of energy barriers of lithium carbon dioxide batteries under different conditions for batteries with different compositions, wherein (a) is comparative example 1, (b) is comparative example 2, and (c) is embodiment 3;

[0019] Figure 5 It curves of lithium carbon dioxide batteries with and without lithium iodide under light-dark cycle irradiation;

[0020] Figure 6 The cycle performance of the photovoltaic auxiliary cell without adding LiI (the cell assembled in Comparative Example 1);

[0021] Figure 7 The cycle performance of the photovoltaic auxiliary cell with added LiI (the cell assembled in Example 3);

[0022] Figure 8 The material of Example 3 has a lithium carbon dioxide battery at 0.01 mA cm -2 The cycle curve below;

[0023] Fig. 9 The rate performance of the lithium carbon dioxide battery at different current densities under the conditions of illumination and no illumination for the material of Example 3;

[0024] Fig.10 The overpotential of the lithium carbon dioxide battery at different current densities under the conditions of illumination and no illumination for the material of Example 3;

[0025] Fig.11 The Bi5O7I photoelectric positive anode light-assisted battery assembled in Comparative Example 1 was 0.01 mA cm -2 Discharge and charge curves of the battery under no light conditions;

[0026] Fig.12 This is a cycle performance diagram of the battery assembled in Comparative Example 2;

[0027] Fig.13 This is the cycle performance diagram of the battery assembled in Comparative Example 3. DETAILED DESCRIPTION

[0028] The following examples will enable those skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0029] Example 1 Preparation of positive electrode material

[0030] 4.85g Bi(NO3)3·5H2O and 1.20g NaOH were dissolved in 50mL distilled water to form a white mixture, which was named Mixture 1A. Then, 4mL of 1mol / L KI solution was added to Mixture 1A and stirred for 30min. This mixture was named Mixture 1B. Mixture 1B was placed in a 100mL Teflon-lined stainless steel autoclave, heated at 180℃ for 24h, cooled to room temperature, and the precipitate was collected by centrifugation, washed 3 times with deionized water and ethanol, respectively, and dried at 60℃ for 24h.

[0031] Figure 1 and Figure 2 The schematic diagram and SEM image of the Bi5O7I photoelectric anode structure with a layered crystal structure prepared in Example 1 of the present invention are respectively shown. Figure 2 It can be seen that [Bi2O2] 2+ Layers are alternately formed with double halogen layers to form Bi5O7I, and the electrode sheet has a diameter of 11 mm.

[0032] Figure 3 This is the XRD pattern of the Bi5O7I photoelectric positive electrode sheet with a layered crystal structure prepared in Example 1 of the present invention. As can be seen from the figure, the XRD pattern of the Bi5O7I photoelectric positive electrode sheet with a layered crystal structure prepared in Example 1 is consistent with the standard card, proving that Bi5O7I was successfully synthesized.

[0033] Bi5O7I was mixed with polyvinylidene fluoride binder (PVDF) and Ketjen Black in n-methyl-2-pyrrolidone liquid, the mass ratio of active material Bi5O7I to PVDF and Ketjen Black was 8:1:1, the slurry was evenly coated on a carbon paper disk, and dried in a vacuum drying oven at 120°C for 12 hours to obtain a bismuth oxyhalide photoelectric positive electrode Bi5O7I / CP.

[0034] Example 2 Preparation of electrolyte

[0035] Measure 2 mL of 1M lithium bis(trifluoromethanesulfonyl)imide-1,3-epoxypentane electrolyte into a glass bottle; then weigh 0.0134 g of anhydrous potassium iodide powder and add it to the above electrolyte, stir thoroughly to dissolve, and then obtain an electrolyte.

[0036] Example 3

[0037] Take the positive electrode of Example 1, 100 μL of the electrode solution prepared in Example 2, lithium foil as the negative electrode, glass fiber as the diaphragm, and the diaphragm pore size is 2.7 μm and the diameter is 19 mm. Assemble the Swagelok type battery in a high-purity carbon dioxide atmosphere glove box (H2O<0.1ppm, O2<0.1ppm).

[0038] The Swagelok-type cell has an air cavity and a transparent window to ensure sufficient light, that is, the cut Bi5O7X / CP photoelectric cathode area is 1.13cm 2 , and the effective lighting area is 0.5cm 2 All cycling performance tests were performed on a Land-CT3001A battery test system with a constant current discharge / charge cycle at a fixed flow rate of 0.05 ml / min CO2. The illumination source used was a 300 W xenon lamp (MC-PF300C, MerryChange, China) that provided light energy in the wavelength range of 280 to 750 nm. The illumination intensity on the Bi5O7I / CP electrode surface was 100 mW cm -2 , potential range is 2.2-5.0V vs.Li / Li + .

[0039] Figure 8 In order to utilize the lithium carbon dioxide battery of Example 3 in which the homogeneous and heterogeneous synergistic catalysis is used with and without the power density of about 100 mW cm -2The cycle life diagram under the condition of a xenon lamp as the light source. Under 250h of illumination, the lithium carbon dioxide battery still shows outstanding cycle stability without increasing polarization. This is because in the presence of the redox medium, the battery has a very stable photoelectric cathode and continuous separation of photogenerated electrons and holes. After 125 cycles, the lithium carbon dioxide battery can still be stably charged and discharged, further indicating that the redox medium (LiI) can still participate in the reaction without being deactivated. Combined with the information in the figure, it can be seen that the present invention can significantly improve the cycle stability of the lithium carbon dioxide battery through the synergistic effect of two catalysts (LiI and Bi5O7I) under the influence of light, indicating that there is a good reversible reaction inside the battery and accelerating the reaction kinetics rate of the CO2 oxidation / reduction reaction in the battery.

[0040] Fig. 9 and Fig.10 The results show that the -2 Rate performance and overpotential at different current densities. Over the entire current density range, the overpotential of the light field is much lower than that of the dark field. In fact, in the discharge state, at 0.1 mA cm -2 At a current density of 0.5 mA cm, the potential of the lithium carbon dioxide battery is lower than 2.0 V. -2 When the current density decreases to 0.01 mAh cm -2 The voltage can also recover to the level of the first five cycles, indicating that the battery has good rate performance. The repeatability of charge and discharge potential and the continuous photoresponsivity indicate that the electrons and holes generated by light can accelerate the CO2RR / CO2ER process under illumination.

[0041] Example 4

[0042] The difference between this embodiment and embodiment 1 is that the added halogen element is Br.

[0043] Example 5

[0044] The difference from Example 1 is that the added halogen elements are all Cl.

[0045] Comparative Example 1

[0046] The difference from Example 1 is that a conventional 1,3-epoxypentane electrolyte containing only bis(trifluoromethanesulfonyl)imide lithium and no halogen lithium salt is used as the battery electrolyte. The battery was assembled according to the method of Example 3 and the performance was tested. The results are as follows: Figure 6 and Fig.11 shown.

[0047] Figure 5 The It curves of lithium carbon dioxide batteries with and without lithium iodide under light-dark cycle irradiation are shown in Figure 1. The recombination rate of carriers can be analyzed from the figure. The more significant photocurrent response of Bi5O7I photocathode with lithium iodide can be attributed to the more densely separated photocharges, indicating that holes are more likely to be combined with I - Reaction instead of recombination with electrons, thus enabling the photocathode to work stably and continuously.

[0048] Figure 6 and Fig.11 The first discharge and charge curves of the lithium carbon dioxide battery prepared in Comparative Example 1 under conditions with and without light. The lithium carbon dioxide battery using Bi5O7I photoelectric anode at a current density of 0.01 mA cm -2 Under the light condition, it shows an ultra-high discharge voltage platform of 3.05V, which exceeds the equilibrium potential of product formation (2.80V vs. Li + / Li), indicating that light energy is continuously output in the form of electrical energy, while it is only 2.65V in the dark. During the reverse charging process, the light-intervention charging voltage dropped to 3.25V, 1.05V lower than 4.30V, indicating that the participation of light-induced holes reduces the electrical energy input of the battery, reaching an energy efficiency of 93.8%, which is significantly higher than 61.6% in the dark. Figure 7 The cycle performance of the photoelectric auxiliary cell (Example 3) with the addition of LiI shows that, compared with the cell without lithium iodide, the solid-liquid synergistic photo-assisted cell has no efficiency drop even after 20 cycles. It is further explained that the present invention can significantly improve the life and stability of the photoelectric positive electrode through the complementary advantages of the two catalysts, reduce the overpotential of the lithium carbon dioxide cell, and improve the electrochemical performance and cycle stability of the cell.

[0049] Comparative Example 2

[0050] The difference from Example 1 is that a conventional carbon nanotube film purchased from Suzhou JEDI Nano Technology Co., Ltd. is used as the positive electrode. The battery is assembled according to the method of Example 3 and the performance test is performed. The results are as follows: Fig.12 shown.

[0051] As can be seen from the figure, when only LiI is used as a heterogeneous catalyst, the battery's first cycle charge and discharge overpotential exceeds 1.6V. As the number of cycles increases, the battery quickly becomes polarized, seriously affecting the battery's cycle stability and life.

[0052] Figure 4The schematic diagram of the energy barrier of lithium carbon dioxide batteries under different conditions using batteries assembled using Comparative Example 1, Comparative Example 2 and Example 3 shows that the energy barrier of the lithium carbon dioxide battery without a redox medium in Comparative Example 1 increases as the photoelectric cathode fails, and the battery operation becomes increasingly difficult; the energy barrier of the lithium carbon dioxide battery with a redox medium but without a photoelectric cathode in Comparative Example 2 is very high, and the battery operation is difficult; the energy barrier of the lithium carbon dioxide battery with both a redox medium and a photoelectric cathode in Example 3 is greatly reduced, and there is no obvious change as the battery operates, and the battery performance is significantly improved.

[0053] Comparative Example 3

[0054] The difference from Example 1 is that a conventional carbon nanotube film purchased from Suzhou JEDI Nano Technology Co., Ltd. is used as the positive electrode, and a conventional 1,3-epoxypentane electrolyte containing only bis(trifluoromethanesulfonyl)imide lithium and no halogen lithium salt is used as the battery electrolyte. The battery is assembled according to the method of Example 3, and the performance test is carried out. The results are as follows: Fig.13 shown.

[0055] As can be seen from the figure, the battery prepared in Comparative Example 3 undergoes rapid polarization after the number of cycles exceeds 30. This is because the difficult-to-decompose discharge product lithium carbonate continues to accumulate on the positive electrode, resulting in a large attenuation of battery performance. After 40 cycles, the charging platform exceeds 4.5V, the overpotential is about 2V, and the battery performance has obviously declined significantly.

[0056] In summary, the bismuth oxyhalogen substances selected in the present invention as p-type semiconductors produce abundant electron-hole pairs under the action of the light field, which significantly reduces the formation and decomposition difficulty of Li2CO3 during the charge and discharge process. With the incorporation of halogen lithium salts, the photocathode is more likely to react with holes at the solid-liquid interface. The photocurrent response of the Bi5O7I photocathode to lithium iodide is more significant, so that the photocathode can work stably and continuously. In addition, halogen lithium salts also contribute to carrier separation. Compared with batteries that do not contain lithium iodide, the solid-liquid synergistic light-assisted battery did not show a decrease in efficiency even after 20 cycles. It shows that the complementary advantages of the two catalysts can significantly improve the life and stability of the photocathode, reduce the overpotential of the lithium carbon dioxide battery, improve the electrochemical performance and cycle stability of the battery, and have good application prospects.

[0057] The above is only a specific implementation of the present application. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. The protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A lithium carbon dioxide battery with homogeneous and heterogeneous synergistic catalysis, comprising a positive electrode, a separator, a negative electrode and an electrolyte, characterized in that: The positive electrode is a bismuth oxyhalide photoelectric positive electrode Bi5O7X / CP, the electrolyte is an organic ether electrolyte added with a lithium salt, and the negative electrode is a lithium foil, wherein the lithium salt includes lithium bistrifluoromethanesulfonyl imide with a final concentration of 1 mol / L and LiX with a final concentration of 0.05 mol / L, and X is Cl, Br or I.

2. A lithium carbon dioxide battery with homogeneous and heterogeneous synergistic catalysis according to claim 1, characterized in that: The diaphragm is a glass fiber diaphragm GF / D.

3. A lithium carbon dioxide battery with homogeneous and heterogeneous synergistic catalysis according to claim 1, characterized in that: The organic ether electrolyte comprises a mixture of one or more of cyclopentane, diethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

4. A lithium carbon dioxide battery with homogeneous and heterogeneous synergistic catalysis according to claim 1, characterized in that: The bismuth oxyhalide photoelectric positive electrode Bi5O7X / CP is prepared by mixing active material Bi5O7X, polyvinylidene fluoride binder PVDF and Ketjen Black in a mass ratio of 8:1:1 and adding them into n-methyl-2-pyrrolidone liquid to form a uniform slurry, which is then coated on a carbon paper disc and dried in a vacuum drying oven at 120°C for 12 hours.

5. A lithium carbon dioxide battery with homogeneous and heterogeneous synergistic catalysis according to claim 1, characterized in that: The preparation method of Bi5O7X is as follows: Bi(NO3)3·5H2O and NaOH are dissolved in distilled water to form a white mixture; KX solution is then added to the white mixture, stirred for 30 minutes, heated at 180°C for 24 hours, cooled to room temperature, centrifuged to collect the precipitate, washed with deionized water and ethanol three times respectively, and dried in a drying oven at 60°C.

6. A lithium carbon dioxide battery with homogeneous and heterogeneous synergistic catalysis according to claim 5, characterized in that: The final concentration of Bi(NO3)3 in the white mixture was 0.2 mol / L, the final concentration of NaOH was 0.6 mol / L, and the final concentration of KX was 0.08 mol / L.

7. A lithium carbon dioxide battery with homogeneous and heterogeneous synergistic catalysis according to claim 1, characterized in that: The working environment of the homogeneous and heterogeneous synergistic catalytic lithium carbon dioxide battery is as follows: the area of ​​the cut bismuth oxyhalogen photoelectric positive electrode Bi5O7X / CP is 1.13cm 2 , and the effective lighting area is 0.5cm 2 , the flow rate of CO2 is 0.05mL / min.

Citation Information

Patent Citations

  • Modified LiNi1 / 2Mn3 / 2O4 cathode material prepared by coating with lithium ion conductor Li2MO3 (M=Ti, Si or Zr) and preparation method thereof

    CN103413930A

  • Lithium ion power battery electrolyte and lithium ion secondary battery

    CN107611479A

  • Lithium oxygen battery electrolyte using molybdenum pentachloride as redox medium and preparation and application thereof

    CN109193030A

  • Bismuth oxyhalide aqueous zinc ion secondary battery positive electrode and preparation method and application thereof

    CN110416531A

  • Novel battery and preparation method thereof

    CN110931867A